Revitalisasi Konstitusional Berbasis Pancasila Dalam Penghapusan Presidential Threshold - Aditya Andela Pratama; Kholifatul Muna; Zico Junius Fernando; Ariesta Wibisono Anditya (Badan Pembinaan Ideologi Pancasila, 2025)
The Presidential Threshold provision has been a controversial debate on the limits of judicial intervention into electoral system design. The Constitutional Court's decision No. 62/PUU-XXII/2024 striking down the provision marked a significant change in Indonesia's constitutional landscape, and presented an opportunity to broaden political participation and strengthen inclusive democracy. In reality, however, this decision raises concerns about the potential for political fragmentation and weakened effectiveness in governance. This research uses a normative juridical method with conceptual, case, and historical approaches. The results of this study show that the Constitutional Court's decision is in line with the values of Pancasila and the principle of people's sovereignty, as well as opening a new discussion space on the balance between political representation and effectiveness in government. The abolition of the presidential threshold is not only seen as a constitutional matter, but also as part of an ongoing process in shaping a democratic system that is more in line with Indonesian values. The abolition is a constitutional revitalization effort based on the principles of Pancasila, particularly in ensuring popular sovereignty, social justice, and open political access for all citizens.